Volatilitas Pasar Modal Syariah Dan Indikator Makro Ekonomi: Studi Banding Malaysia dan Indonesia - Muhammad Syafii Antonio; Hafidhoh Hafidhoh; Hilman Fauzi (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
This study attempts to examine the short-term and long-term relationship among selected global and domestic macroeconomic variables from each country (Fed rate, crude oil price, Dow Jones Index, interest rate, exchange rate and inflation). Two main indexes will be analyzed namely Jakarta Islamic Index (III,) FTSE Bursa Malaysia Hijrah Shariah Index (FHSI). The methodology used in this study is vector error correction model (VECM) for the monthly data starting from January 2006 to December 2010. The result shows, all selected macroeconomic variable have significantly affect both Islamic stock market FHSI and JII, Analysis of FE VD (Forecast Error Variance Decomposition).The result also shows that the amount of influence of global and domestic macroeconomic variables on Islamic capital market volatility in Indonesia and Malaysia have different sequences. Volatility of III is influenced by variables sequentially OIL, BIR, ERI, DOW, CPI and FED. While volatility of FHSI sequentially influenced by variables of FED, OIL, MYR, CPIM, DOW and ERM. Different result is due to two main factors: the difference macroeconomic stability and the amount of global intervention on the economy.